2018
DOI: 10.4274/jcrpe.4774
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Blood Transfusion on Insulin Sensitivity and Pancreatic β-Cell Function in Children with β-Thalassemia/Hemoglobin E Disease

Abstract: Objective:To assess the acute effects of blood transfusion on insulin sensitivity and pancreatic β-cell function in thalassemia patients.Methods:Fifty children and adolescents with β-thalassemia/HbE disease were enrolled in a prospective cohort study. Hemoglobin, serum ferritin and oral glucose tolerance test (OGTT) were performed prior to, and one week after blood transfusion. Insulin sensitivity indices [homeostatic model assessment (HOMA) of insulin resistance (HOMA-IR), whole body insulin sensitivity index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Disturbances of glucose homeostasis, ranging from mild glucose intolerance to overt diabetes mellitus, and hyperinsulinism were reported in young adult patients with thalassemia and have been attributed to iron overload, HCV infection, anemia, and chronic liver disease. 66,67 An acute effect of blood transfusion on insulin sensitivity and β-cell function in patients with thalassemia has been reported by Wankanit et al 68 Alcohol and Tobacco. Alcohol and iron are known prooxidants, and oxidative stress is known to play an essential role in the development of several diseases, including cancer.…”
Section: Pathophysiology Past and Recent Issuesmentioning
confidence: 90%
“…Disturbances of glucose homeostasis, ranging from mild glucose intolerance to overt diabetes mellitus, and hyperinsulinism were reported in young adult patients with thalassemia and have been attributed to iron overload, HCV infection, anemia, and chronic liver disease. 66,67 An acute effect of blood transfusion on insulin sensitivity and β-cell function in patients with thalassemia has been reported by Wankanit et al 68 Alcohol and Tobacco. Alcohol and iron are known prooxidants, and oxidative stress is known to play an essential role in the development of several diseases, including cancer.…”
Section: Pathophysiology Past and Recent Issuesmentioning
confidence: 90%
“…Previous studies have shown that blood transfusion in thalassemia patients causes acute increases in serum ferritin and hemoglobin which contribute to an increase in insulin resistance. [27] We postulate that this could partly account for the development of postoperative hyperglycemia among our patients who received blood transfusions, given the relatively high prevalence of thalassemia in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Wankanit et al showed a 14% prevalence of abnormal OGTT in HbEβ-thalassemia patients. [28] e prevalence of AGH in both β-thalassemia major and HbEβ-thalassemia patients is seen to have an earlier onset than in the age-matched general population.…”
Section: Discussionmentioning
confidence: 86%